Flavor meets function: Red grape juice (Vitis vinifera L.) enrichment enhances the microbiological, chemical, and sensory quality of yogurt - Intan Rahma Sari; Muhammad Saefi; Didik Wahyudi (Green and Tropical Laboratory for Sustainability, 2025)
Background: One of the main challenges in yoghurt production is the potential for microbiological contamination, especially by Coliform bacteria. Meanwhile, red grapes (Vitis vinifera L.) are known to have bioactive content that has the potential to improve yoghurt quality by not only suppressing coliform bacteria, but also increasing Lactic Acid Bacteria (LAB), reducing pH and acid levels, and improving sensory preferences. Objectives: This study aims to investigate the microbiological, chemical, and organoleptic characteristics of yoghurt after the addition of red grape juice (Vitis vinifera L.). Methods: This study is an exploratory study conducted with four concentrations: K0 (without the addition of red grape juice), K1 (5%), K2 (10%), and K3 (15%). The parameters observed include the number of Coliform bacteria, LAB, lactic acid levels, pH, and organoleptic tests. Data analysis of the total number of LAB, lactic acid levels, the number of coliform bacteria and pH values ​​was carried out descriptively quantitatively. Meanwhile, the results of the organoleptic test were compared between groups using the Kruskal-Walli’s test statistics. Results: The results showed that K3 produced the highest total BAL of 2.71 × 10⁹ CFU/mL. The lowest number of Coliforms of 3 apm/mL was produced by K2, in accordance with the yoghurt quality standards based on SNI 2981:2009. The highest lactic acid content was recorded in K3 of 1.89%, while the lowest pH value was achieved in K3 with a value of 4.00. Organoleptic tests showed that K2 and K3 gave the highest average values ​​for taste, aroma, and color attributes, with a tendency for consumer preference to increase along with the addition of fruit juice concentration. Conclusion: The most favorable results were obtained at concentrations of 10% (K2) and 15% (K3), which provided an optimal balance between sensory quality, microbiological safety, and chemical stability of the product. The addition of red grape juice increased the functional value of yoghurt in microbiological, chemical, and organoleptic aspects.